2023
DOI: 10.3390/foods12091819
|View full text |Cite
|
Sign up to set email alerts
|

Yolk Fatty Acid Content, Lipid Health Indices, and Oxidative Stability in Eggs of Slow-Growing Sasso Chickens Fed on Flaxseed Supplemented with Plant Polyphenol Extracts

Abstract: Previous attempts to increase the level of flaxseed in hens’ diet for the production of n-3 polyunsaturated fatty acids (n-3 PUFAs)-enriched eggs have been commonly associated with undesirable effects on production efficiency, lipid health indices, and oxidative stability of eggs, requiring adequate research attention. This study investigated the effects of feeding a moderate level of flaxseed (FS) and plant polyphenol extracts (PPEs) on fatty acid content, oxidative stability, and lipid health indices in eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…A study conducted for 26 wk, starting at initiation of laying period (wk 16) until mid of peak production (wk 42), showed that moringa oleifera leaves (0.5, 1, and 1.5%) significantly improved the PUFA profile, especially the total of n-3 compared to control diet ( Sharmin et al, 2021 ). This effect was recently confirmed by other authors ( Tadesse et al, 2023 , Mierlita et al, 2024 ). Moreover, these results show that the action of the enzyme in the formation and depletion of fatty acids starts from the first stage of egg deposition.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A study conducted for 26 wk, starting at initiation of laying period (wk 16) until mid of peak production (wk 42), showed that moringa oleifera leaves (0.5, 1, and 1.5%) significantly improved the PUFA profile, especially the total of n-3 compared to control diet ( Sharmin et al, 2021 ). This effect was recently confirmed by other authors ( Tadesse et al, 2023 , Mierlita et al, 2024 ). Moreover, these results show that the action of the enzyme in the formation and depletion of fatty acids starts from the first stage of egg deposition.…”
Section: Discussionsupporting
confidence: 85%
“…A significant increase in total n-3 fatty acids (1.40 versus 1.18) and significant decrease in total n-6 fatty acids (29.85 versus 30.65) was observed only for RL1 yolks compared to RL0 yolk samples. Although rosehip leaves cannot be considered sources of fat, it was reported that plant feed additives, through their antioxidant profile have a protective effect on PUFA from oxidative breakdown ( Vlaicu et al, 2021 ; Tadesse et al, 2023 ). Another reason for fatty acids alteration in eggs is the hens age and hybrid used.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional modifications may also encompass the mineral composition and vitamin content [ 3 , 4 , 5 ]. The fatty acid profile of the yolk depends primarily on its composition in the feed, which allows easy modification, especially towards the proportion of mono- and poly-unsaturated fatty acids [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Egg fatty acids, especially polyunsaturated fatty acids (PUFAs), are important in poultry production for improving the health and productivity of birds, and are useful for improving cardiovascular health and cognitive function of human. Many studies have showed that the influence of dietary supplementation of vegetable seeds and oils, fish oil and natural antioxidants on the fatty acids composition of eggs (3)(4)(5)(6). Another way to improve the health quality of eggs is through reducing the content of cholesterol and trimethylamine (TMA).…”
Section: Introductionmentioning
confidence: 99%